EFEKTIVITAS TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP KECEMASAN PASIEN KANKER PAYUDARA STADIUM II DAN III - Ningsih, Santi Fitria; Karim, Darwin '; Sabrian, Febriana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this study wasÂ  to determine the effectiveness of Emotional Freedom Technique (EFT) therapy to anxiety of breast cancer stage II and IIIÂ  patients . This study used "Quasy experiment" design with "Non-equivalent control groupâ€. The study was conducted in Anyelir room and Cendrawasih roomÂ  in Arifin Achmad Hospital Pekanbaru. Purposive sampling technique with inclusion criteria was used to recruit 30 respondents. The instrument in this study used in both groups was a questionnaire that has beentested for validityandrealibility. TheÂ  data were analyzedÂ  using paired sample t-test and independent sample t-test. The results in experimental group showed p value (0.005) <Î± (0.05) which means that EFT was effective to decrease anxiety in breast cancer patient. Based on this result, it isÂ  recommended that health provider especially nurses to use Emotional Freedom Technique (EFT)Â  therapy as one of non pharmacological therapy to decrease anxiety. KeywordsÂ  : Anxiety, breast cancer, Emotional freedom technique